Assessing the feasibility of screening and providing brief advice for alcohol misuse in general dental practice: a clustered randomised control trial protocol for the DART study. Issue 10 (6th October 2015) - Ntouva, Antiopi; Porter, Jessie; Crawford, Mike J; Britton, Annie; Gratus, Christine; Newton, Tim; Tsakos, Georgios; Heilmann, Anja; Pikhart, Hynek; Watt, Richard G
Abstract : Introduction: Alcohol misuse is a significant public health problem with major health, social and economic consequences. Systematic reviews have reported that brief advice interventions delivered in various health service settings can reduce harmful drinking. Although the links between alcohol and oral health are well established and dentists come into contact with large numbers of otherwise healthy patients regularly, no studies have been conducted in the UK to test the feasibility of delivering brief advice about alcohol in general dental settings. Methods and analysis: The Dental Alcohol Reduction Trial (DART) aims to assess the feasibility and acceptability of screening for alcohol misuse and delivering brief advice in patients attending National Health Service (NHS) general dental practices in North London. DART is a cluster randomised control feasibility trial and uses a mixed methods approach throughout the development, design, delivery and evaluation of the intervention. It will be conducted in 12 NHS general dental practices across North London and will include dental patients who drink above the recommended guidance, as measured by the Alcohol Use Disorders Identification Test (AUDIT-C) screening tool. The intervention involves 5 min of tailored brief advice delivered by dental practitioners during the patient's appointment. Feasibility and acceptability measures as well as suitability of proposed primary outcomes of alcohol consumption will be assessed. Initial economic evaluation will be undertaken. Recruitment and retention rates as well as acceptability of the study procedures from screening to follow-up will be measured. Ethics and dissemination: Ethical approval was obtained from the Camden and Islington Research Ethics Committee. Study outputs will be disseminated via scientific publications, newsletters, reports and conference presentations to a range of professional and patient groups and stakeholders. Based on the results of the trial, recommendations will be made on the conduct of a definitive randomised controlled trial. Trial registration number: ISRCTN81193263.